Predicción de la relación diámetro-altura total de Ocotea aciphylla (Nees) Mez. Según tamaño de muestra en bosque natural. Puerto Almendra, Loreto, Perú, 2021 - Candiotti Noriega, Roy Paul (2023)
The research was developed at the Faculty of Forest Sciences - UNAP, in San Juan Bautista, Maynas, Loreto. Its objective was to determine the prediction of the total diameter-height relationship in Ocotea aciphylla (Nees) Mez. according to sample size in natural forest. Puerto Almendra, Loreto, Peru. The data were of the diameter and total height of the trees of the species under study with DAP ? 10 cm; the samples were, Sample 1: 30 individuals distributed in diameter classes; Sample 2 = 50 data distributed in diametric class; Sample 3 = Representative sample with diameter class (40 data) and Representative sample without diameter class (40 data). The results of the diameter - total height relationship defined the power allometric model because it had a better fit and the degree of relationship was excellent; The equations for the prediction of the diameter-total height relationship are: Sample 1: Y= 3,477 x (t 0,495); Sample 2: Y= 3,300 x (t 0,529); Representative Sample With diameter class: Y= 3,300 x (t0,532); Representative Sample Without diameter class: Y= 2.776 x (t 0,598).